Towards a new generation of Digital Repository of Scientific Institutes - Betański, Błażej (Qualitative and Quantitative Methods in Libraries, 2020)
Digital Repository of Scientific Institutes (DRSI) was established in 2010 as a collective initiative of 16 scientific institutes from Poland. The main objective of this initiative is to provide for the research community a country-level, multidisciplinary digital repository composed of archival materials, scientific publications, research documentation and cultural heritage content. DRSI is maintained by the Polish scientific institutes, forming the DRSI Consortium. In 2018 a country-level, EU co-funded project named OZwRCIN, was initiated in order to improve DRSI. The project sets out several objectives that can be reduced to a general statement about sharing, archiving and disseminating public sector information. More than 140 thousands of digital objects will be provided in the scope of the project, using new technologies and innovative approaches. The project specifically aims at providing research datasets. To manage digitisation activities and make the digital content available online the DRSI uses infrastructure and tools developed by Poznan Supercomputing and Networking Center (PSNC). PSNC is an ICT-focused R&D institution, infrastructure provider and operator of the Polish Optical Internet PIONIER. PSNC is a technical partner in the OZwRCIN project. This article discusses in details the key concept of the DRSI, its infrastructure, the software stack as well as organisation of the consortium itself.